2004
DOI: 10.1590/s0036-46652004000200006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of human cytomegalovirus genetic diversity in different patient populations in Costa Rica

Abstract: SUMMARYSeroprevalence of HCMV in Costa Rica is greater than 95% in adults; primary infections occur early in life and is the most frequent congenital infection in newborns. The objectives of this study were to determine the genetic variability and genotypes of HCMV gB gene in Costa Rica. Samples were collected from alcoholics, pregnant women, blood donors, AIDS patients, hematologyoncology (HO) children and HCMV isolates from neonates with cytomegalic inclusion disease. A semi-nested PCR system was used to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…In our study, we observed slightly higher incidence rates of gB1 and gB2 genotypes (50.0 %) and lower rates for the gB3 genotype (8.3 %), while no gB4 genotype was found among either the fetuses or the newborns. Similar frequencies of HCMV genotypes were reported also for Costa Rican and Indian infants [20, 27]. Differences observed between our results and the results of the study of newborns and infants from Southern Poland may not be significant, since both study groups were relatively small.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, we observed slightly higher incidence rates of gB1 and gB2 genotypes (50.0 %) and lower rates for the gB3 genotype (8.3 %), while no gB4 genotype was found among either the fetuses or the newborns. Similar frequencies of HCMV genotypes were reported also for Costa Rican and Indian infants [20, 27]. Differences observed between our results and the results of the study of newborns and infants from Southern Poland may not be significant, since both study groups were relatively small.…”
Section: Discussionsupporting
confidence: 68%
“…Glycoprotein B1 (33%) predominates in Thai patients and no gB4 was detected. In different patient populations in Costa Rica, gB2 was the most frequent gB genotype encountered (73%) [15] . In a Cuban cohort of patients with different HCMV diseases, gB2 was the most prevalent (38%), followed by gB1 (30%), and mixed HCMV infections (16%) [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 organizes the gB genotyping studies alphabetically by study continent and country, as well as by patient profile. All five genotypes have been detected in Asia, Europe, and North America, however their geographic distribution differs: gB-1 is the most prevalent genotype in Asia and Egypt ; gB-1 and gB-2 are frequently detected in North America [58,[100][101][102][103][104][105][106][107][108][109]; gB-2 is the most extensively sampled genotype in Latin America [110][111][112][113][114][115][116][117][118][119][120][121][122][123]; whereas gB-1, gB-2, and gB-3 are commonly observed across Europe (with the exception of Serbia where gB-4 is the most prevalent genotype) [24,55,57,59,. Although the majority of HCMV-positive individuals who participated in these studies carried gB-1, gB-2, and/or gB-3 genotypes, the association between any particular gB genotype and disease severity is inconsistent among studies [24,55,[59][60][61][62][63][64][65][66][67][68]…”
Section: Gbmentioning
confidence: 99%